Pengaruh Sustainability Report Dan Profitabilitas Terhadap Return Saham - Baskara Ilham Prista; Wahidatul Husnaini; Robith Hudaya (Fakultas Ekonomi dan Bisnis Unram, 2026)
This study aims to examine the effect of sustainability reporting and profitability on stock returns in manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2021 period. The study is grounded in signaling theory, which explains that information disclosed by companies, including sustainability disclosures and profitability ratios, serves as a signal to investors in making investment decisions. The data used in this study are secondary data obtained from the official website of the Indonesia Stock Exchange and the respective companies’ websites. The sampling method employed was purposive sampling, resulting in a total of 126 observations. The independent variables in this study are sustainability reporting, measured using the GRI Standards index, and profitability, proxied by Return on Equity (ROE), while the dependent variable is stock return. The data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression analysis. The results indicate that sustainability reporting has a negative and significant effect on stock returns, while profitability proxied by ROE does not have a significant effect on stock returns. A limitation of this study lies in its relatively short observation period; therefore, future research is recommended to use a longer time horizon to obtain more comprehensive results.